Optical deposition of carbon nano-particles on waveguides - Nguyen, Duy Anh. (2012)
The novel optical properties of carbon-based materials such as nanotubes or graphene have recently attracted significant interest. They have been demonstrated to have a fast saturable absorption with subpicosecond recovery times in the near infrared communication band. A variety of techniques have been implemented in order to integrate carbon nanotubes (CNT) into fiber/waveguide devices. However, one of their drawbacks is the handling method. Recently, a novel technique was demonstrated for optically-driven deposition of carbon nanotubes on fibers using optical tweezer effect on nano particles.